Study of nuclear morphometry in the cytologic evaluation of thyroid neoplasms - Joyce Thomas; Tulsi Shyam Chhadi; Hirkani Chhadi (Journal of Pathology of Nepal)
Background: Nuclear morphometry is purported to allow better differentiation between various thyroid lesions beyond what is offered by conventional cytology. The present study was conducted to evaluate the nuclear morphometric parameters in fine needle aspirates of thyroid neoplasms and to study their role in differentiating benign and malignant thyroid neoplasms.